2016
DOI: 10.1016/j.neuroimage.2015.11.055
|View full text |Cite|
|
Sign up to set email alerts
|

Can sliding-window correlations reveal dynamic functional connectivity in resting-state fMRI?

Abstract: During the last several years, the focus of research on resting-state functional magnetic resonance imaging (fMRI) has shifted from the analysis of functional connectivity averaged over the duration of scanning sessions to the analysis of changes of functional connectivity within sessions. Although several studies have reported the presence of dynamic functional connectivity (dFC), statistical assessment of the results is not always carried out in a sound way and, in some studies, is even omitted. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
595
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(622 citation statements)
references
References 45 publications
24
595
0
3
Order By: Relevance
“…Another essential point pertaining to any sliding window analysis is the extent to which observed FC fluctuations are truly the reflection of dynamic changes in brain connectivity, rather than artefactual correlates of the employed methodology (Hindriks et al, 2016). In the resting‐state literature, several approaches have been suggested for this purpose, from the computation of FC across separate subjects (Keilholz, Magnuson, Pan, Willis, & Thompson, 2013) to the generation of appropriate null data with disrupted dynamics (Betzel, Fukushima, He, Zuo, & Sporns, 2016; Leonardi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another essential point pertaining to any sliding window analysis is the extent to which observed FC fluctuations are truly the reflection of dynamic changes in brain connectivity, rather than artefactual correlates of the employed methodology (Hindriks et al, 2016). In the resting‐state literature, several approaches have been suggested for this purpose, from the computation of FC across separate subjects (Keilholz, Magnuson, Pan, Willis, & Thompson, 2013) to the generation of appropriate null data with disrupted dynamics (Betzel, Fukushima, He, Zuo, & Sporns, 2016; Leonardi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies using resting-state fMRI in humans reported that the temporal fluctuation of FC cannot be distinguished from that in a model assuming stationary FC and statistical sampling error [23,24]. Applying the same analysis to the mouse data, we found that, in both neuronal calcium and hemodynamic signals, the temporal dynamics of FC were not fully explained by stationary FC [16].…”
mentioning
confidence: 83%
“…Dynamic functional connectivity among the 80 nodes was computed over a 44.64 s tapered (rectangle convolved with a Gaussian) sliding window incremented 0.72 s over 14.4-minute node timeseries 81 . In the absence of information about the timescale of dynamic fluctuations in connectivity, the probability of detecting such fluctuations in resting fMRI data is optimized for a sliding window approximately 50 s in duration 56 . Because the data included more features than observations, the pairwise connectivity matrix during each time window was computed as a regularized precision matrix 32,[82][83][84] .…”
Section: Methodsmentioning
confidence: 99%